PRINSIP PROPORSIONALITAS DAN GOVERNANCE TERHADAP ALOKASI DAN TRANSFER RISIKO DALAM SKEMA KERJASAMA PUBLIC-PRIVATE PARTNERSHIP (PPP) - yuniarti yuniarti; Fifi Junita (Yuridika, 2017)
The high level of Foreign Direct Investment (FDI) is also supported by the availability of infrastructure to the remote area where the investment will be implemented. However, with limited funds from both APBN and APBD, infrastructure development can not be fully done by the government. Therefore, the government will cooperate with the investor (private) in the implementation of infrastructure development known as public private partnership. The main problem in implementing PPP is the allocation of risk to PPP projects. The different bargaining positions between the government and the private sector resulted in the fact that most of them impose risks on private parties (private). Implementation of PPP is closely related to the emergence of various risks including and not limited to regulatory risks, force majeure, etc. If there is no risk allocation arrangement proportionally based on governance principles, it weakens the pattern of PPP cooperation in Indonesia. PPP as one form of risk sharing in infrastructure investment should not release the role and government support to private parties / investors. Even in practice, PPP implementation in Indonesia only relies on BOT (Build Operate and Transfer) scheme which is expected to minimize government support in project implementation. This will ultimately lead to project failure.